Efforts to Shape Akhlakhul Kharimah Student Through Moral Education (Comparative Study of Elementary School and Madrasah Ibtidaiyah in Palembang) - Noptario Noptario; Sutrisno Sutrisno (Al-Aulad: Journal of Islamic Primary Education, 2023)
Moral education is a learning material that must be truly understood and applied by students in everyday life. Because morals determine the personality and character of students. In the current era, students often encounter moral crises caused by several factors. A teacher must be able to solve this problem so that students have commendable morals and can achieve learning goals. This study uses qualitative research methods by carrying out data collection techniques through interviews, previous research and expert opinions as reinforcement. While the data analysis technique is using data reduction, data display and drawing conclusions. This research reveals that both MI and SD provide education on commendable morals, but MI has more moral education because it is taught in three subjects, namely fiqh, akidah akhlak and al-Quran hadith. Whereas in elementary school the subjects that contain moral education are in PAI but thematic and PKn lessons also often discuss moral education. SD and MI also have programs to guide student morals, starting from students shaking hands with the teacher every morning, Friday imtaq at MI and reading juz amma at the beginning of every month at SD.Keywords: elementary school, madrasah ibtidaiyah, moral education.